Karakterisasi Laju Pengeringan Gabah DenganDengan Al - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT After harvesting technology was an important knowledge for Indonesian rice farmer. In the raining season especially, the paddy has to be dried within 6 days, or the paddy has to be sold for very cheap price. In order to solve the problem, a new drying technology has to be developed, utilizing direct contact method The study has been conducted partially, by experimentally characterizing heat and mass transfer process for paddy drying implementing forced convection. In this paddy drying study employing electrical heater, it could be shown that the drying rate of the paddy was affected by the flow velocity, temperature difference and the layer thickness. The equation of the drying rate had also been derived. The rate was not only affected by those variables but also by the vertical distance between the paddy layers. It was suspected that the drying process was categorized as drying process with constant rate in slightly turbulent flow